scRNA-seq and scATAC-seq analyses highlight the role of TNF signaling pathway in chronic obstructive pulmonary disease model mice - Qiang Zhang; Li Zhou; Lindong Yuan; Ruihua Zhang; Shanshan Pan; Xizi Wang; Lili Yi; Fengjiao Yuan; Xianchao Guo; Mingliang Gu; Yan Wang; Xiaodong Jia (PLoS ONE, 2025)
Chronic obstructive pulmonary disease (COPD) is a prevalent and progressive form of respiratory disease in which patients exhibit persistent respiratory damage affecting the alveoli and/or airway due to exposure to toxic gases or particulate matter. C57BL/6 mice were exposed to cigarette smoke and lipopolysaccharide to establish a COPD model mice, followed by scATAC (Assay for Transposase Accessible Chromatin) sequencing and scRNA sequencing of lung tissue samples. The resultant data revealed consistent findings between scATAC-seq and scRNA-seq regarding cell types, differentially expressed genes, and signaling pathways in COPD model mice. Tumor necrosis factor (TNF) signaling pathway enrichment was evident in the scRNA-seq and scATAC-seq datasets, with similar trends in monocytes/macrophages, dendritic cells, and B cells. In COPD model mice, significant tumor necrosis factor receptor 1 (TNFR1) upregulation and high levels of activity related to cellular communication were observed, and significant increases in Il1b, Csf1, and Bcl3 site accessibility were evident in cells. These findings suggest that the TNF signaling pathway maybe associated with COPD.